2013
DOI: 10.1590/s1678-69712013000100003
|View full text |Cite
|
Sign up to set email alerts
|

Valores que motivam mulheres de baixa renda a comprar produtos de beleza

Abstract: O artigo tem como objetivo identificar valores individuais que motivam mulheres de baixa renda, mesmo vivendo com severas limitações financeiras, a comprar produtos de beleza, que poderiam, à primeira vista, ser considerados itens supérfluos. O modelo de cadeia meios-fim de Gutman (1982) e os tipos de valores de Rokeach (1973) e Floch (1990) constituíram sua base conceitual. Foram conduzidas entrevistas em profundidade, empregando a técnica laddering (REYNOLD; GUTMAN, 1988), com 17 mulheres de baixa renda resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 28 publications
2
7
0
5
Order By: Relevance
“…Therefore, women are compelled to consume and nourish that self-image, which assists in the constitution of their femininity and their acceptance (Livramento, Hor-Meyll, & Pessôa, 2013). Beauty, although not the only desired attribute of femininity, was also the object of a study by Machado--Borges (2008) that sought to analyze how a printed magazine of Brazilian national circulation represented women and plastic surgery and how femininity would associate with class and race issues.…”
Section: Contemporary and Desired Femininitymentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, women are compelled to consume and nourish that self-image, which assists in the constitution of their femininity and their acceptance (Livramento, Hor-Meyll, & Pessôa, 2013). Beauty, although not the only desired attribute of femininity, was also the object of a study by Machado--Borges (2008) that sought to analyze how a printed magazine of Brazilian national circulation represented women and plastic surgery and how femininity would associate with class and race issues.…”
Section: Contemporary and Desired Femininitymentioning
confidence: 99%
“…Women are led to perceive themselves as alien to those images and to apprehend "the weight that appearance and image have in contemporary culture" (Nunes, 2008, p. 49). In a study performed with a low-income female audience, Livramento et al (2013) identified values that lead those women to buy beauty products, even without financial conditions to provide their own food, as well as other basic needs. For the millennials generation, those conditions also involve a growing interest in information on fashion and beauty products, based on the social pressure associated with an indication of success or social belonging (Fernandez & Karhawi, 2015).…”
Section: Contemporary and Desired Femininitymentioning
confidence: 99%
See 1 more Smart Citation
“…Por conta disto, este estudo buscou investigar as características e o perfil de consumo feminino da base da pirâmide universitária do Rio de Janeiro no mercado dermocosmético, que figura como uma categoria intermediária de produtos para a pele, entre os medicamentos e os cosméticos, e funciona à base de ingredientes biologicamente (Livramento;Hor-Meyll;Pessoa, 2013;Messeder;Reis, 2011). A 2 O retorno do investimento na beleza/aparência já foi comprovado, na prática, por essas mulheres (Livramento;Hor-Meyll;Pessoa, 2013;Messeder;Reis, 2011).…”
Section: A Beleza E a Base Da Pirâmideunclassified
“…A 2 O retorno do investimento na beleza/aparência já foi comprovado, na prática, por essas mulheres (Livramento;Hor-Meyll;Pessoa, 2013;Messeder;Reis, 2011). A 3 Apesar do aumento do consumo, as escolhas ainda precisam ser bem-pensadas e controladas (Vicente, 2012a;Machado, 2012).…”
Section: A Beleza E a Base Da Pirâmideunclassified